The Routledge companion to Native American literature
1 online resource (xxvi, 524 pages)
Keywords: "The Routledge companion to Native American literature engages the multiple scenes of tension -- historical, political, cultural, and aesthetic -- that constitutes a problematic legacy in terms of community identity, ethnicity, gender and sexuality, language, and sovereignty in the study of Native American literature. This important and timely addition to the field provides context for issues that enter into Native American literary texts through allusions, references, and language use. The volume presents over forty essays by leading and emerging international scholars and analyses: - regional, cultural, racial and sexual identities in Native American literature - key historical moments from the earliest period of colonial contact to the present - worldviews in relation to issues such as health, spirituality, animals, and physical environments - traditions of cultural creation that are key to understanding the styles, allusions, and language of Native American Literature - the impact of differing literary forms of Native American literature. This collection provides a map of the critical issues central to the discipline, as well as uncovering new perspectives and new directions for the development of the field. It supports academic study and also assists general readers who require a comprehensive yet manageable introduction to the contexts essential to approaching Native American Literature. It is essential reading for anyone interested in the past, present and future of this literary culture" --